2014
DOI: 10.17126/joralres.2014.022
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the use of teaching videos in preclinical training of Chilean dentistry students, 2013.

Abstract: Abstract:The use of educational videos is a valuable tool in preclinical dental training, as long as the pedagogical objectives match the appropriate learning stage. Accordingly, this teaching innovation suggests the realization of three types of didactic videos inserted in a specially designed pedagogical methodology for the preclinical cycle. After half a semester of use, quantitative results yielded a positive perception in relation to the promotion of evaluation criteria and conflictual tone development. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…The proposal of continuous learning, however, is not limited to students who are completing their graduation. The association of lectures and videos in pre-clinical subjects showed an increase in student performance compared to students who participated only in traditional lecture classes, considering the experience useful and advantageous (Goset and Espinoza, 2013;Shigli et al, 2017;Amrithaa et al, 2020). Likewise, the present students considered the video useful for learning the proposed theme.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The proposal of continuous learning, however, is not limited to students who are completing their graduation. The association of lectures and videos in pre-clinical subjects showed an increase in student performance compared to students who participated only in traditional lecture classes, considering the experience useful and advantageous (Goset and Espinoza, 2013;Shigli et al, 2017;Amrithaa et al, 2020). Likewise, the present students considered the video useful for learning the proposed theme.…”
Section: Discussionmentioning
confidence: 98%
“…This auxiliary tool also intended to fill in the absence of similar materials found on the websites of the universities surveyed during stage 1 of this study. As previously reported, the availability of videos may be restricted to private platforms at universities, on the so-called intranet (Goset and Espinoza, 2013) and, therefore, the lack of available content on the subject should be interpreted with caution. Since the video produced on this study presents a generic content of common interest to all dentistry students, regardless of their institution, it is understood that its wide dissemination would be a good practice.…”
Section: Discussionmentioning
confidence: 99%
“…Research showed that students found clinical concepts difficult to grasp since the teaching was more theoretical, and faculty found it difficult to correlate ideal situations to what actually happened in clinic 19 . Research also showed that demonstrations and videos 40 as well as interactive sessions were critical in understanding the clinical material. However, even when video demonstrations were provided, students reported that videos should not replace clinical demonstrations 18,40–42 .…”
Section: Discussionmentioning
confidence: 99%
“…Research also showed that demonstrations and videos 40 as well as interactive sessions were critical in understanding the clinical material. However, even when video demonstrations were provided, students reported that videos should not replace clinical demonstrations 18,40–42 . In addition, faculty respondents felt that they were “giving half the knowledge as students are not exposed to patients” and felt that “lack of clinical exposure” was an obstacle when training students 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Todos los estudiantes del curso estuvieron expuestos a los tres tipos de demostración, los cuales fueron usados para demostrar distintos procedimientos simulados que se realizaron en el primer semestre del curso. Al finalizar el primer semestre, se aplicó un cuestionario estructurado de 7 preguntas de autoaplicación, que fue construido a partir de los utilizados en estudios anteriores (Shah et al, 2015;Goset y Espinoza 2014;Smith et al, 2012;Alqahtani et al, 2015;Kon et al, 2015;Kapoor et al, 2015) para medir la percepción de los estudiantes en aspectos educativos, técnicos y de preferencia personal. Para cada pregunta del cuestionario el estudiante debía escoger uno de los tres recursos didácticos usados para la demostración.…”
Section: Métodosunclassified